Environmental footprinting of agri-food products traded in the European market - Popova, Olha; Koval, Viktor; Vdovenko, Nataliia; Sedikova, Iryna; Nesenenko, Pavlo; Mikhno, Inesa (Frontiers in Environmental Science, 2022)
Sustainable food principles and requirements established by the European Union are becoming a standard for all foodstuffs available on the EU market, and it should be taken into account by countries exporting agri-food products, such as Ukraine. The aim of this article is to generalize European milestones for defining sustainable foodstuffs, revealing their key differences from ecological/organic products, differentiating products in the carbon footprint level, substantiating challenges for exports of agri-food products to the EU in terms of positioning their sustainability. The European market features an increasing differentiation of agri-food products in terms of sustainability and ecology, particularly carbon, footprint indicators, which are examined in this article. More stringent monitoring of chemical pesticide and antimicrobial residues in products exported to the EU could be a challenge as the use of these products is expected to be reduced by 50% by 2030. This study substantiates the risks for agricultural production and exports in Ukraine caused by the differentiation of agri-food products in their sustainability indicators, enhancement of monitoring the level of residues of pesticides and active ingredients of veterinary drugs in agri-food products, limitation of agri-food, and agricultural raw material exports to the EU because of heavy greenhouse gas emissions during crop cultivation to produce biofuel. This study analyzes the economic growth of agri-food products that will take place only in the case of avoiding the impoverishment of natural resources, which is formalized based on Robert Higgins’ model. The results of the research can be used for further strategic planning in the field of agricultural production with enviromental regulation.